El marketing digital y la atención al cliente en la empresa Plasti-Centro de la ciudad de Guayaquil - Conde Cajo, Andrea Belen (2024)
ABSTRACT: The objective of this research project is to propose digital marketing strategies that encompass all digital tools to enhance and optimize customer service at Distributor Plasti-Centro Ecuador, located in Guayaquil.  Inductive and deductive methods, along with a non-experimental study design, were employed to examine the study variables in their real-world context. Two types of research were conducted: descriptive research to specify the study phenomenon, and field research to gather data directly from the facts.  The population and sample consisted of customers of Distributor Plasti-Centro, who were surveyed to obtain real data and understand their perception regarding the company’s customer service. The findings from statistical analysis led to the deduction that the company should implement digital marketing strategies through social media and a website to keep their customers satisfied and thereby increase sales.    Keywords: marketing, attention, satisfaction, strategies, company.